Frequency of Malignant Pleural Mesothelioma in Patients with Massive Pleural Effusion Admitted in Pulmonology Ward Mardan Medical Complex Mardan - Farmanullah; Ali, Sajjad; Bahadur, Zeeshan; Ahmad, Imtiaz (Indus Journal of Bioscience Research, 2025)
Background: Malignant pleural mesothelioma is an uncommon cancer that has a strong link to asbestos exposure. It is not well understood why mesothelioma develops in patients with large pleural effusion. This study provided the frequency of malignant pleural mesothelioma in patients with massive pleural effusion and identified demographic and clinical risk factors associated with its development. Objective: To determine the frequency of malignant pleural mesothelioma in patients with massive pleural effusion admitted in pulmonology ward Mardan Medical Complex Mardan. Study Design: Cross-sectional study. Duration and Place of Study: The study was conducted from December 15, 2024, to May 15, 2025, at the Department of Pulmonology, Mardan Medical Complex, Mardan. Methodology: A total of 112 patients of age 18 to 70 years with massive pleural effusion were selected. Pleural tissue specimens were obtained via percutaneous needle biopsy or thoracoscopic biopsy, and histopathological analysis with immunohistochemical staining was used to diagnose mesothelioma. Results: The mean age of participants was 47.67 ± 14.11 years, with a male predominance (61.6%). Mesothelioma was diagnosed in 9 patients (8%). Statistically significant associations were found between mesothelioma and older age (>50 years), male gender, BMI >30 kg/m², symptom duration >12 weeks, and rural residency. Conclusion: Malignant pleural mesothelioma is a significant cause of massive pleural effusion in patients over 50 years of age, predominantly affecting males with a higher BMI.